2020
DOI: 10.1101/2020.07.26.20162453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the patterns of repeated testing for COVID-19: Association with patient characteristics and outcomes

Abstract: Importance The diagnostic tests for COVID-19 have a high false negative rate, but not everyone with an initial negative result is re-tested. Michigan Medicine, being one of the primary regional centers accepting COVID-19 cases, provided an ideal setting for studying COVID-19 repeated testing patterns during the first wave of the pandemic. Objective To identify the characteristics of patients who underwent repeated testing for COVID-19 and determine if repeated testing was associated with patient characteristic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…Studies have found disparities in SARS–CoV‐2 testing among underserved populations, such as marginalized ethnic groups and individuals of low socioeconomic classes (11,39,40). Our study results are in line with previous studies that showed increased SARS–CoV‐2 testing among patients with chronic diseases (14,41). Having any IMID was associated with 20% higher chances of being tested for SARS–CoV‐2 compared to non‐IMID patients, even after adjusting for other confounding factors including comorbidities, and testing was higher across all IMID groups, with ORs ranging from 1.11 to 1.42.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have found disparities in SARS–CoV‐2 testing among underserved populations, such as marginalized ethnic groups and individuals of low socioeconomic classes (11,39,40). Our study results are in line with previous studies that showed increased SARS–CoV‐2 testing among patients with chronic diseases (14,41). Having any IMID was associated with 20% higher chances of being tested for SARS–CoV‐2 compared to non‐IMID patients, even after adjusting for other confounding factors including comorbidities, and testing was higher across all IMID groups, with ORs ranging from 1.11 to 1.42.…”
Section: Discussionsupporting
confidence: 93%
“…Although in Italy [ 18 ] as elsewhere [ 26 ], the use of healthcare services by PWMS during the pandemic was reduced, this may not be true for the prescription of swabs. This result is in line with what has been observed among patients with immune-mediated inflammatory diseases [ 21 ] and other chronic diseases [ 27 , 28 ]. Higher rates of testing may be explained by several factors, including the perception of a higher risk of COVID-19 by PWMS and their doctors, general higher health awareness of PWMS, higher attention to symptoms, and the need to test for SARS-CoV-2 before hospital admission or out-patient visits.…”
Section: Discussionsupporting
confidence: 92%